Feeding Behaviour, Performance and Nutrient Utilization of Different Growing Goat Breeds Fed Creep Feed - Astuti, Dewi Apri; Permana, sep Tata; Stevani, Rori; Ramadhania, Tariza; Khotijah, Lilis; Fassah, Dilla Mareistia (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
This study was aimed to evaluate feeding behaviour, performance and nutrient utilization of goats fed different form of creep feed.  Twelve local growing goats (average age 5 months, BW 20.0±1.57 kg), consisting of six Etawah crossbred and six Senduro goats were  included in the study. The study was conducted in a factorial completely randomized block design of 2x2. The first factor was type of  creep feed form (mash and pellet), and the second factor was type of goat breed (Etawah crossbred and Senduro). The ration consisted  of 70% creep feed containing BSF (black soldier fly) meal and oil plus 30% elephant grass. The variables observed were feeding behaviour,  nutrient consumption, digestibility, blood metabolites, and performance. Results showed that there was no interaction between the  creep feed forms and the goat breeds in any of the variables. The form of creep feed had a significant effect (p
Keywords: Behaviour; Creep feed; Etawah crossbreds; Mash; Pellet; Senduro